Kudal Commission of Inquiry on Gandhi Peace Foundation and Other Organisations Final Report - Planning Commission (Planning Commission, 1987)
The present report is the Final Report of the Commission. With this the Commission has submitted seven reports in all to the Union Government. This Report consists of six chapters and five appendices. Chapter II deals with the findings of the Commission in respect of 29 cases which have been finalized after the Sixth Interim Report. The Commission has, during its tenure, completed inquiry proceedings in 180 cases and given its findings in 167 cases.
Final Report
Planning Commission Library Government of India